Non-governmental organizations (Ngos) and human capital utilization in internally displaced persons (Idps) camps in Borno State, Northeast Nigeria: examining the available potential - Sadat, Shehu; Wan Jaafar, Wan Munira; Rosnon, Roslan; Md Khir, Azlina (Gokmen Arslan, 2022)
This paper examines the major issues hampering the maximum utilization of human capital in the internally displaced persons (IDPs) camps in Borno State, Northeast Nigeria. Data for the paper were sourced from documents and analyzed using the content analysis technique. Based on available evidence, the paper found that utilization of available human capital by the NGOs in the IDPs camps are largely hindered by the lack of transparency and competency, as well as the complexity in the humanitarian efforts of the NGOs. The paper further found that one of the greatest challenges to the utilization of faced by the NGOs in an attempt to ultimately utilize its human capital is its adjustment to change. Thus, the paper concludes that the NGOS need some amendments to enable it to achieve its agenda while ensuring maximum utilization of the available human capital in the IDPs camps. Also, it concludes that human capital utilization remains a valuable aspect of humanitarian needs of the youth in the state as it guarantees representation across the board. Thus, the paper recommends maximum of utilization of available resources in training the IDPs, as it will assist the NGOs in meeting their needs.